An ultrasensitive gray-imaging-based quantitative immunochromatographic detection method for fumonisin B1 in agricultural products. (October 2017) - Tang, Xiaoqian; Li, Peiwu; Zhang, Zhaowei; Zhang, Qi; Guo, Jingnan; Zhang, Wen
Abstract: Fumonisins (FBs) are widely found in rice, maize, peanut, wheat, and other agricultural products. These have been detected using a chromatography technique, whereas the rapid assay by a highly sensitive monoclonal antibody is minimally reported. Herein, a highly sensitive monoclonal antibody (7A11) was successfully developed by hybridoma technique. The 50% inhibition concentration (IC50 ) of 7A11 monoclonal antibody was 0.32 ng/mL in an optimized buffer. The cross-reactivity between fumonisin B1 and fumonisin B2, B3 was 4.3% and 12.8%, respectively. Based on the newly developed 7A11 antibody, a high sensitivity indirect competitive enzyme-linked immunosorbent assay (icELISA) and gold nanoparticles-based gray imaging quantification immunoassay (GNPs-GI) were established. The analytical range of icELISA was 0.08–1.38 ng/mL and that for GNPs-GI was 0.24–15 ng/mL. Both the methods showed adequate recoveries (80.0–105.8% for icELISA and 78.5–115.2% for GNPs-GI) in spiked samples. Compared to high-performance liquid chromatography (HPLC), icELISA and GNPs-GI indicated reliability that could be used for further detection of fumonisin B1 in agricultural products. Highlights: A high sensitive novel monoclonal antibody against fumonisin B1 was achieved. A indirect competitive enzyme-linked immunosorbent assay (icELISA) was established for fumonisin B1 detection. A gold nanoparticles-based gray imaging quantification immunoassay (GNPs-GI) was developed for fumonisin B1 detection. The icELISA and GNPs-GI performed rapidly assay for fumonisin B1 in agricultural products.